PLANNING PREFABRICATED HOMES USING THE FASTER, BETTER, CHEAPER CONCEPT - Agung, Devie; Tutuko, Pindo; Budiyanto, Hery; Poerwoningsih, Dina (International Conferences SDGs 2030 Challenges and Solutions, 2030)
Prefabrication as a technology that has long been used in Europe, have a big potential to help fulfill the housing backlog in Indonesia. Project time and cost efficiency along with multiple other benefits have proven that prefabrication system is a valid alternative to the conventional construction system. One of the biggest problem delaying the implementation was the perception of construction practitioners and home buyers about the structural and visual quality, and a prefabricated home owners’satisfaction when compared to a conventionally built home owners’. Faster, Better, Cheaper concept may be the guide to planning a house building project that can be finished faster, be more cost efficient, while achieving higher user satisfaction.